To what extent is Blue Labour a coherent campaigning group? - Aitchison, Arthur (2023)
This thesis will analyse the coherence of Blue Labour as a campaigning group, focusing on what I deem to be the five most important subjects for discussion. What this thesis found was that although Blue Labour is, in several aspects, not coherent in their campaigning, they are in fact a vital part of maintaining the Labour Party’s connection to those northern ‘red wall’ communities which the Party holds so dear. My analyse of Blue Labour is assessed through the theoretical framework of Michael Freeden as well as through an Interpretivist approach argument that ideology is not static and can adapt and change over time.